Qur'anic Consumption Ethics and SDGs: Reconstructing the Contextual Interpretation of Qur'an 17:26–27 as a Critique of Modern Consumerism - Ach. Zayyadi; Wildana Dwi Lestari; Salih Abdulrahman Alsounusi (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study aims to reconstruct the Qur’anic ethics of consumption in QS. Al-Isra’ (17): 26-27 and examine its relevance to contemporary consumerism and the Sustainable Development Goals (SDGs). Theoretical framework: The research is grounded in the theoretical framework of Islamic moral economy and ethical sustainability, using the hermeneutical approach of Ma’na cum Maghza to connect the textual meaning of the Qur’an with its contemporary social significance. Literature review: Previous studies have examined the concept of tabdhir (wastefulness) in Qur’anic interpretation and Islamic economic ethics; however, most remain normative and rarely integrate Qur’anic ethical principles with modern consumer culture or the global sustainability discourse. Methods: This study employs qualitative library research with textual and contextual analysis of QS. Al-Isra’ (17): 26-27 based on classical and contemporary Qur’anic exegesis and interdisciplinary literature. The analysis follows three stages: historical meaning, universal significance, and contextual reinterpretation. Results: The findings reveal that Qur’anic consumption ethics are built upon three core principles: wealth as a social trust, moderation in consumption, and the prohibition of wastefulness (tabdhir). These principles function as a moral framework that critiques modern consumerism while simultaneously supporting responsible consumption and equitable resource distribution. Furthermore, the study demonstrates that these ethical principles align with several SDGs, particularly SDG 12, SDG 1, SDG 10, and SDG 16, by promoting sustainable consumption, social justice, and economic balance. Implications: This study contributes theoretically by integrating contextual Qur’anic interpretation with sustainability discourse, offering a value-based framework for sustainable development grounded in Islamic ethical principles. Novelty: This study integrates the Ma'na cum Maghza approach with sustainability discourse by reconstructing Qur'an 17:26–27, offering a Qur'anic ethical framework for critiquing modern consumerism and promoting responsible consumption aligned with the SDGs.